Legasitas Perceraian di Luar Pengadilan dalam Perspektif Wahbah Az-Zuhaili dan Kompilasi Hukum Islam di Indonesia - Iskandar, Muhammad; Ningrat, Muhammad Afdhol Kusuma (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Extrajudicial divorce still occurs in society, raising issues regarding the legal status of the divorce and the protection of the rights of the husband, wife, and children. This study aims to analyze and compare the validity of extrajudicial divorce according to the perspectives of Wahbah Az-Zuhaili and the Compilation of Islamic Law (KHI), as well as the associated legal consequences under Indonesian positive law. The study employs a library research method with a normative-juridical approach. Data were obtained from Wahbah Az-Zuhaili’s *Al-Fiqh al-Islami wa Adillatuhu*, the KHI, relevant legislation, and scholarly literature. A descriptive-comparative analysis was conducted to identify similarities and differences between the two perspectives. The findings indicate that, according to Wahbah Az-Zuhaili, divorce does not always require a judicial ruling. Under certain conditions, *talak* (repudiation) and *khulu’* (divorce initiated by the wife) can occur without a court ruling, whereas other forms of divorce—such as those resulting from a lack of maintenance, physical defects, harm (*mudarat*), abandonment, imprisonment, or *talak ta’asuf* (arbitrary/abusive repudiation)—require judicial intervention. Conversely, the KHI mandates that divorce proceedings take place before the Religious Court. The primary difference lies in the status of the judicial ruling as a prerequisite for a valid divorce. Wahbah Az-Zuhaili’s jurisprudence allows for certain extrajudicial divorces, whereas the KHI requires a judicial process to secure legal recognition.